Towards a global phylogeny of freshwater mussels (Bivalvia: Unionida): species delimitation of Chinese taxa, mitochondrial phylogenomics, and diversification patterns - Huang, Xiao-Chen (Molecular phylogenetics and evolution, 2019)
The Yangtze River Basin in China is one of the global hotspots of freshwater mussel (order Unionida) diversity with 68 nominal species. Few studies have tested the validity of these nominal species. Some taxa from the Yangtze unionid fauna have not been adequately examined using molecular data and well-positioned phylogenetically with respect to the global Unionida. We evaluated species boundaries of Chinese freshwater mussels, and disentangled their phylogenetic relationships within the context of the global freshwater mussels based on the multi-locus data and complete mitochondrial genomes. Moreover, we produced the time-calibrated phylogeny of Unionida and explored patterns of diversification. COI barcode data suggested the existence of 41 phylogenetic distinct species from our sampled 40 nominal taxa inhabiting the middle and lower reaches of the Yangtze River. Maximum likelihood and Bayesian inference analyses on three loci (COI, 16S, and 28S) and complete mitochondrial genomes showed that the subfamily Unioninae sensu stricto was paraphyletic, and the subfamily Anodontinae should be subsumed under Unioninae. In addition, we described two new tribes (Aculamprotulini tribe nov. and Lepidodesmini tribe nov.) in the subfamily Unioninae and one new genus (Parvasolenaia gen. nov.) in the subfamily Gonideinae. Molecular dating analysis suggested freshwater mussels diversified at 346.1Mya (HPD=286.6-409.9). The global diversification rate for Unionida was estimated to be 0.025species/Myr. Our study found only a single well-supported rate shift in Unionida diversification, occurring at the base of the subfamily Ambleminae. The evolution of active host-attraction may have triggered the burst of speciation in Ambleminae, and the environment and geography of the Mississippi River Basin likely sustained this radiation.